Developing of devices and methods of timekeeping for training 4 x 100 m relay teams - Галица, Виталий Иванович; Качанов, Петр Алексеевич (Technology audit and production reserves, 2015)
This work is devoted to the development of the method of timekeeping cross sections at a distance during training 4 x 100 m relay teams. Specificity of training is that the measured time of running athlete with the baton over zone of 20m. By virtue of the fact that the transmitting and receiving cross section of start and end of zone, resulting in redundancy of temporal information. Existing methods of timing do not allow fixing it. It is developed a method for a single time field and measuring equipment, allowing providing a preliminary analysis of the received signals, providing higher reliability and accuracy of the data. It minimizes the appearance of artifacts that are conceptually solves the problem of reliability and accuracy of information transfer and ultimately the effectiveness of training athletes.